Live-attenuated Japanese encephalitis virus inhibits glioblastoma growth and elicits potent antitumor immunity - Qi, Zhongbing; Zhao, Jing; Li, Yuhua; Zhang, Bin; Hu, Shichuan; Chen, Yanwei; Ma, Jinhu; Shu, Yongheng; Wang, Yunmeng; Cheng, Ping (Frontiers in Immunology, 2023)
Glioblastomas (GBMs) are highly aggressive brain tumors that have developed resistance to currently available conventional therapies, including surgery, radiation, and systemic chemotherapy. We here investigated the oncolytic properties of a live attenuated Japanese encephalitis vaccine strain (JEV-LAV) virus for GBM treatment. JEV-LAV displayed oncolytic activity against GBM tumor cells in vitro and inhibited their growth in vivo. Moreover, it effectively prolonged the survival of tumor-bearing mice. Mechanistically, JEV-LAV increased CD8+ T cell infiltration into tumor tissues and remodeled the immunosuppressive GBM microenvironment that is non-conducive to immunotherapy. Consequently, in combination with an immune checkpoint inhibitor, JEV-LAV therapy improved the response of aPD-L1 blockade therapy against GBM. The safety of intracerebrally injected JEV-LAV in animals further supported the clinical use of JEV-LAV for GBM treatment.